Diseño de un Plan de Manejo Ambiental en la microcuenca del Rio Yasepán de la Parroquia Cebadas, Cantón Guamote, Provincia de Chimborazo. - Chávez Heredia, Luis Alberto (2020)
This research paper is focused on conserving the shores of Yasepan River, it is developed before to notable environmental deterioration, over exploitation of natural resources, pollution of hydric resources that contributes to climate change, deforestation, this paper aims to elaborate an Environmental Management Plan in the shores of Yasepan River through elaborating a diagnose or baseline, socio-environmental evaluation using methodologies that allow gathering information through descriptive research, bibliographic and documented methodology and the qualitative method for designing Environmental Management Plan. Research techniques were carried out according to on-site visits and direct observation as well as through on-site visits, observation and gathering information from written documents, such as texts, brochures , files, newspapers, research papers and the PDyOT belonging to Cebadas Parish, in addition to perform the linear transepts that allowed to gather information on fauna and flora, determining that the main cause of environmental deterioration, pollution of hydric resource is due to the lack of environmental policies that prevent the advance of the agricultural borders, burning grasslands, and lack of Environmental Management Plan on the mountain ecosystem, which leads to immediate application of this research to contribute to sustainable socio-environmental management.